AN ANGIOTENSIN-CONVERTING ENZYME INHIBITOR AND CALCIUM ANTAGONIST COMBINATION IN PHARMACOTHERAPY OF ARTERIAL HYPERTENSION - L. L. Kirichenko; S. V. Gatsura; A. N. Golosova; K. V. Ovsyannikov; O. V. Budik; A. V. Fedorov (Кардиоваскулярная терапия и профилактика, 2014)
The paper focuses on the justification for preferential administration of antihypertensive combination therapy. Pharmacotherapeutic features of starting the treatment with a combination of angiotensin-converting enzyme inhibitors (ACEI) and calcium antagonists (AC) are reviewed. The authors also present the latest evidence on the ACEI/AC combination effects on such vascular parameters as microcirculation and endothelial dysfunction.